Potent adjuvant effect elicited for tumor immunotherapy by a liposome conjugated pH-sensitive polymer and dendritic cell-targeting Toll-like-receptor ligand. Issue 10 (1st March 2022) - Watanabe, Shunichi; Yuba, Eiji; Akazawa, Takashi; Wijewardana, Viskam; Kakihara, Yuka; Azuma, Ayaka; Hagimori, Kenji; Kanegi, Ryoji; Hatoya, Shingo; Inoue, Norimitsu; Inaba, Toshio; Sugiura, Kikuya
Graphical abstract: Highlights: A liposome with DC-targeting TLR ligand and pH-sensitive polymer was developed. The liposome significantly activates DCs and is selectively incorporated into DCs. The liposome significantly enhances antigen-presentation of DCs on MHC class I. Immunization using the liposome augments tumor antigen-specific cytotoxicity. Vaccination therapy using the liposome suppresses and eliminates the tumor. Abstract: The generation of DCs with augmented functions is a strategy for obtaining satisfactory clinical outcomes in tumor immunotherapy. We developed a novel synthetic adjuvant comprising a liposome conjugated with a DC-targeting Toll-like-receptor ligand and a pH-sensitive polymer for augmenting cross-presentation. In an in vitro study using mouse DCs, these liposomes were selectively incorporated into DCs, significantly enhanced DC function and activated immune responses to present an epitope of the incorporated antigen on the major histocompatibility complex class I molecules. Immunization of mice with liposomes encapsulating a tumor antigen significantly enhanced antigen-specific cytotoxicity. In tumor-bearing mice, vaccination with liposomes encapsulating a tumor antigen elicited complete tumor remission. Furthermore, vaccination significantly enhanced cytotoxicity, targeting not only the vaccinated antigen but also the other antigens of the tumor cell. These results indicate that liposomes are an ideal adjuvant to develop DCs with considerably high potential to elicit antigen-specific immune responses; they are a promising tool for cancer therapy with neoantigen vaccination.